2019
DOI: 10.15537/smj.2019.1.23754
|View full text |Cite
|
Sign up to set email alerts
|

The role of anxious temperament in patients with allergic rhinitis

Abstract: Objectives: To evaluate the depressive and anxiety levels in allergic rhinitis (AR) and to investigate the relationship between depression and anxiety symptoms and depressive and anxious temperament features. Methods: The study design is cross-sectional. The study was conducted between January 2017 and January 2018. Patients (n=101) diagnosed with AR and healthy controls (n=74) were included in this study. All participants were assessed with the Beck Depression Inventor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Forty studies were further excluded after full-text reading, leaving 24 primary studies included in the systematic review . Among the included papers, 13 studies solely reported results on depression (19,(21)(22)(23)(28)(29)(30)(31)(32)36,37,39,41) , one study solely reported results on anxiety (35) and 10 studies presented results on both depression and anxiety (18,20,(24)(25)(26)(27)33,34,38,40) . Of these 24 primary studies, 12 studies (20,(26)(27)(28)(29)(30)(34)(35)(36)38,39,41) presented OR from multivariable regression models and were included in our main analyses -11 studies (20,(26)(27)(28)(29)(30)34,36,38,39,41) provided results from multivariable models assessing the association between A...…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty studies were further excluded after full-text reading, leaving 24 primary studies included in the systematic review . Among the included papers, 13 studies solely reported results on depression (19,(21)(22)(23)(28)(29)(30)(31)(32)36,37,39,41) , one study solely reported results on anxiety (35) and 10 studies presented results on both depression and anxiety (18,20,(24)(25)(26)(27)33,34,38,40) . Of these 24 primary studies, 12 studies (20,(26)(27)(28)(29)(30)(34)(35)(36)38,39,41) presented OR from multivariable regression models and were included in our main analyses -11 studies (20,(26)(27)(28)(29)(30)34,36,38,39,41) provided results from multivariable models assessing the association between A...…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of the 23 included primary studies assessing the association between AR and depression (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(36)(37)(38)(39)(40)(41) . These studies were published between 1991 and 2019 and their sample sizes ranged from 88 to 240 million participants, resulting in a total of more than 243 million participants.…”
Section: Studies Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Experts in otolaryngology pointed out symptom score, disease control score, quality of life score, medication score as important outcomes. Meanwhile, they stressed the importance of mental status in related to AR, and introduced several scales to assess mental health in AR patients [24][25][26][27].…”
Section: Consensus Conference With Delphi Surveymentioning
confidence: 99%
“…There are various types of indicators to assess the quality of life of AR patients, such as RQLQ (Rhinoconjunctivitis Quality of Life Questionnaire)[47, 48], RAPP (RhinAsthma Patient Perspective)[49,50], SF-36 (Medical Outcome Study Questionnaire Short Form 36 Health Survey)[51,52], etc. The mental health score is another critical concern in AR management[26], scales such as BDI (Beck Depression Inventory)[24] and PHQ-2 (Patient Health Questionnaire-2)[53] have been mentioned. Medication score is commonly used to re ect the e cacy of complementary therapy, it could be described as RMS (Rescue Medication Score)[54,55] or MS (Medication Score)[56].…”
mentioning
confidence: 99%